A Matemática na educação inclusiva para DI’s: concepções e divergências entre as políticas da inclusão e a realidade escolar - Silva, Daianne Naier da (2019)
The main objective of this work was to conduct a study directed to the teaching of mathematics in inclusive education focusing on students with intellectual disabilities, in order to understand how this teaching-learning process has happened in inclusive classrooms (especially in the classroom). mathematics) of mainstream schools, as well as the knowledge and behavior of leading and supporting teachers in special education. This whole study was conducted by collecting data on how inclusion has been advancing (or not) since its implementation to the present day, using as source documents that legalize and guide the work of all professionals working in inclusive education. in Brazil and the State of Goiás, emphasizing mainly the role of teachers in this process. The research work uses as qualitative approach the investigative methodology and as tools for this investigation the documental analysis (of the laws, decrees and guidelines for the inclusion today), use of questionnaires (for support teachers and conductors) and a case study (of a support teacher) based on an interview with her. Relevant information on intellectual disability is also found in the work regarding its causes, diagnosis and treatment and researchers' notes, together with our theoretical references to demonstrate the possibility of building an inclusive mathematics for students with intellectual disabilities. Finally, the paper reflects on the observations made by the teachers involved in the research regarding inclusive education in their theory and what happens in practice.